A comprehensive publication (“Finansinė analizė“ [“Financial Analysis”], a textbook, by Prof. Dr. Habil. J. Mackevičius, PhD L. Giriūnas, PhD R. Valkauskas) - Raziūnienė, Reviewed by Daiva (Ekonomika, 2015)
Not only the competitive and dynamic but also the complex and challenging business environment of the world and the European Union markets triggers the need to easily measure and comprehend the available business information as well as to communicate it in a clear manner. The language of business is most commonly the language of numbers, the skillful command of which is based on the fundamental principles of informatikon gathering, processing, perception, and use. [...]